Sistem Informasi Geografis Fasilitas Kesehatan di Tuntungan Berbasis Android - Fajrillah; Lusiah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The use of Android phone data frames is growing rapidly in today's world. He is known for his ability to retrieve data quickly and accurately, especially during crises. His one of human information needs is information about medical facilities. The purpose of this article is to provide an Android-based application that helps an individual obtain data from his Tuntungan Public Health Authority in various ways. The method used to improve the framework in this review is his waterfall model consisting of five phases: requirements identification, system design, code preparation, program testing, and program implementation. In addition, program development using Visual Studio Code, Flutter SDK, Mobile Emulator, Mobile Emulator and Firebase integration as information base. During this inspection, the use of the Geographic Information System